Re-irradiation for head and neck squamous cell carcinoma - Rony Benson; Prashant Giridhar; Bhanu Prasad Venkatesulu; Supriya Mallick; Mohd Waseem Raza; Goura Kishor Rath (Journal of the Egyptian National Cancer Institute, 2017)
Introduction: Local recurrences after curative treatment have a potential for cure with salvage surgery or with re-irradiation. Methods: We reviewed the PubMed for articles published in English with key words squamous cell carcinoma, recurrent, re-irradiation, prognostic factors to find relevant articles describing prognostic factors, re-irradiation, and outcome for recurrent head and neck squamous cell carcinoma. Results: Various factors including age, performance status, time for recurrence, previous radiation dose volume and site of recurrence, previous use of chemotherapy are all prognostic factors in recurrent head and neck squamous cell carcinoma. Surgery is feasible in very select subgroup of patients and must be done when feasible. Re-irradiation with the aid of modern sophisticated technology is safe and confers durable and clinically meaningful survival benefit. Re-irradiation in head and neck recurrent squamous cell carcinoma may provide an expected median survival of 10–12 months. Chemotherapy may be added along with radiation in the recurrent setting. Conclusion: Treatment approaches may have to be personalized. Re surgery must be done in all patients in whom it is feasible. In patients in whom surgery is not feasible, re-irradiation must be evaluated as a therapeutic option especially in patients with limited volume recurrence.